Potential Benefits of Artificial Intelligence-Based Instruction Implementation in English Academic Writing Course: A Case Study at an Indonesian Private University - Setiadi, Muhammad Astrianto (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study describes the potential benefits of implementing AI-based instruction in an English academic writing course by revealing the views from the lecturers' perspective. This research uses a qualitative descriptive case study to investigate the phenomenon of using AI in higher education in the Indonesian context. During data collection, interviews were conducted to gather lecturers' perspectives on the use of artificial intelligence in English academic writing courses. Thematic analysis was used to interpret the data. Based on the findings, there are five benefits of implementing artificial intelligence in English academic writing courses. The results showed that the lecturers showed a positive perception towards the use of this platform. Integrating artificial intelligence provides prospects for personalized learning and feedback, increased efficiency and productivity of lecturers, improved quality of teaching and learning, innovation in teaching methods, and preparation of students for the digital era.